2011
DOI: 10.1021/la200942u
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Organo-Highly Charged Mica

Abstract: The interlayer space of the highly charged synthetic Na-Mica-4 can be modified by ion-exchange reactions involving the exchange of inorganic Na + cations by surfactant molecules, which results in the formation of an organophilic interlayer space. The swelling and structural properties of this highly charged mica upon intercalation with n-alkylammonium (RNH 3 ) + cations with varying alkyl chain lengths (R = C12, C14, C16, and C18) have been reported. The stability, fine structure, and evolution of gaseous spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
4
32
0
3
Order By: Relevance
“…These swelling high-charge micas, in which the layer charge can be adjusted, could be highly valuable for the decontamination of harmful divalent and heavy metal cations (Ravella et al, 2008) via ion-exchange reactions and for the selective removal of highly radioactive ions (Alba et al, 2006) and hydrocarbon molecules (Alba et al, 2011).…”
mentioning
confidence: 99%
“…These swelling high-charge micas, in which the layer charge can be adjusted, could be highly valuable for the decontamination of harmful divalent and heavy metal cations (Ravella et al, 2008) via ion-exchange reactions and for the selective removal of highly radioactive ions (Alba et al, 2006) and hydrocarbon molecules (Alba et al, 2011).…”
mentioning
confidence: 99%
“…The (001) diffraction peak for the as-prepared sample was observed at 3.3°, which corresponds to the basal spacing of 2.5 nm. Considering this repeating unit and the length of 1-hexadecylamine (~2.0 nm), 17 the hexadecylamine might be arranged into monolayer with a tilt angle between tin oxide particles. Successive thermal treatments were performed to examine the thermal stability of this sample.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the distribution coefficient, Kd, and the normalized coefficient to the organic content, Kom. The Kd decreases as the alkyl chain increases in parallel with the interlayer water content [19]. According to the values of the logarithms of the normalized sorption coefficients, it is found that the sorption efficiency of organomicas follows the order: C12-Mica-4 > C14-Mica-4 > C16-Mica-4 > C18-Mica-4, indicating that the sorption depends on the chain length of the organic cations.…”
Section: (M=12 14 16 Y 18 Number Of C On the Alkyl Chain)mentioning
confidence: 97%
“…Sheng et al [33], have found that aromatic compounds, due to their flat shape and presence of π-bond, interact strongly with the organic cation in the organoclay, causing a reorientation of the alkyl chains when alkylammonium cations lie parallel to the sheets of silicate and the alkylammonium adopted a vertical position. In Cm-Mica-4 the organization of the alkylammonium cations corresponds to inclined bilayers [19] and thus, phenol sorption do not affect to the arrangement of alkylammonium cations.…”
Section: (M=12 14 16 Y 18 Number Of C On the Alkyl Chain)mentioning
confidence: 99%
See 1 more Smart Citation